"There is no one to pick up the pieces": Sustainability of antibiotic stewardship programs in nursing homes. (26th April 2021) - Seshadri, Sandhya; Felsen, Christina B.; Sellers, Craig R.; Dumyati, Ghinwa K.
Abstract: Objective: To describe nursing home staff experiences and perceptions of the factors that impact the sustainability of an antibiotic stewardship program (ASP). Methods: Using a qualitative descriptive design, semistructured interviews with staff at 9 not-for-profit nursing homes with an established ASP were conducted and audio recorded. De-identified transcriptions of the interviews were coded using a sustainability framework and were analyzed to identify themes. Results: Interviews were conducted with 48 clinical and administrative staff to elicit their perceptions of the ASPs, and 7 themes were identified. ASPs were perceived to be resource intensive and "data driven, " requiring access to and interpretation of data that are not readily available at many nursing homes. Though motivated and committed, ASP champions felt that they could not single-handedly sustain the program. Attending to daily clinical needs (ie, "fires") made it hard to progress beyond implementation and to reach step 2 of sustainability. Longstanding treatment habits by external prescribers and regulations were believed to impede ASP efforts. Partnerships with an external consultant with antibiotic stewardship expertise were considered important, as was the need for internal leadership support and collaboration across disciplinary boundaries. Participants felt that consistent and ongoing education on antibiotic stewardship at all staff levels was important. Conclusions: Although many interconnected factors impact the sustainability of an ASP, nursing homes may be able to sustain an ASP by focusing on 3 critical areas: (1) explicit support by nursing home leadership, (2) external partnerships with professionals with antibiotic stewardship expertise and internal interprofessional collaborations, and (3) consistent education and training for all staff.